The Рroblems and Аpproaches of Russian Тeaching in the Universities of Xin Jiang (Journal of Educational Sciences, 2020)
This paper aims to discuss the existing teaching problems and teaching approches of Rus- sian in Xin Jiang Province universities(People’s Republic of China). The aim of the research is to ana- lyze the methods used for teaching Russian in universities in Xin Jiang. The main problems of teaching Russian in universities in Xinjiang, according to the author, are the lack of experienced and qualified lecturers, unbalanced programs and the lack of a unified methodology. The author predicts that as the partnership and interaction between China and Russia develop, China will need more and more special- ists in the Russian language in the future. The research included a survey of respondents on the quality of Russian language teaching in Xinjiang. The survey involved a total of 590 respondents, studying and teaching Russian language. However, 487 respondents fully completed the questionnaires, so the analy- sis was carried out for this sample. The questionnaire consisted of 18 questions and was divided into 4 parts. The first part is basic information about the respondent; the second part is related to the curricu- lum; the third part is an overview of problems in teaching Russian; the fourth part is the future direction of development and employment.Key words: Russian language teaching methods, level of language proficiency, teaching Russian as a foreign language, comparative education, teaching methods, China.